Combining Ability Analysis of Maize Inbred Lines Suitable For Machine Harvest - YU, Haiyan; Rong, Meiqi; Jiang, Long; LI, Jianming (Bangladesh Journal of Botany, 2023)
Using self selected maize inbred lines and hybrid combinations as test materials, the combining ability of maize hybrids suitable for machine harvest was analyzed. Ten maize inbred lines were selected as female parent (P1) and three inbred lines as male parent (P2). The experiment design of incomplete diallel cross was adopted in this study. The combining ability of 10 agronomic characters such as plant height, ear height, ear grain weight, ear length, ear diameter, number of rows per ear, number of grains per row, 100- grain weight, number of branches in male ear and water content at harvest were analyzed. The present findings revealed that in terms of general combining ability, JM39 was the best in ear length, grain number per row, 100-grain weight, branch number of male ear and water content at harvest, followed by JM35, JM26 and JM28. In terms of specific combining ability, the combination with better performance were JM39×JF167, JM39×JF200 and JM35×JF167. Moreover, JM26, JM28, JM35 and JM39 could be used directly, and the other inbred lines could be improved and reused. Plant height, number of rows per ear, number of grains per row and 100-grain weight should be selected in the early generation, while ear height, ear diameter, number of branches in male ear and water content at harvest should be selected in the late generation. Bangladesh J. Bot. 51(4): 889-895, 2022 (December) Special